Preliminary Kidney Parenchymal Ligation Using Endoloop Ligatures—A Simple Method to Achieve a Trifecta in Laparoscopic Partial Nephrectomy Without Hilar Clamping for Polar Complex Tumors - Komai, Yoshinobu; Gotohda, Naoto; Matsubara, Nobuaki; Takeda, Hayato; Yuasa, Takeshi; Inoue, Masaharu; Yamamoto, Shinya; Yonese, Junji (Urology (Ridgewood, N.J.), 2018)
To describe a novel and simple technique of preliminary kidney parenchymal ligation using Endoloop ligatures during laparoscopic partial nephrectomy (PN) without hilar clamping for polar complex tumor cases. The subjects were 17 patients who had a renal mass with a R.E.N.A.L. nephrometry score ≥7 (7/8/9/10 in 3/6/6/2 patients, respectively) located in the pole of the kidney. Patient-specific 3D reconstructed kidney images were created for preoperative planning in all cases. The renal hilar vessels were meticulously dissected and definitive tumor feeders were sacrificed when the branches directly perfused the peri-tumor area. Following the vascular microdissection, a circumferential cortex-depth incision on the kidney was made all around the tumor. Consequently, several Endoloop ligatures were placed in the incised tumor base to ligate the parenchyma preliminarily. Step-by-step Endoloop tightening facilitated effective parenchymal dissection without the urinary tract. After confirming that the tumor base parenchyma was ligated sufficiently, tumor resection was completed. Neither inner- nor outer-layer renorrhaphy sutures were placed. Perioperative outcomes were satisfactory and all patients had negative surgical margins with no damage in the tumor capsule. Urological complications and renal function lower than predicted at 3 months after surgery involved 1 and 3 cases, respectively. The rate of PN trifecta achievement was 82% (14/17) despite the complexity of the 17 tumors. The current technique helped surgeons achieve the trifecta in patients with polar complex masses treated with laparoscopic PN. Use of this technique can provide surgeons with a bloodless operative field even during PN without hilar clamping.